PERAN BAHASA INGGRIS SEBAGAI BAHASA KEDUA DALAM PEMEROLEHAN BAHASA INDONESIA SEBAGAI BAHASA KETIGA - Abdul Kholiq (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2017)
Cross language influence in third language (L3) acquisition is related to the first (L1) and second language (L2) acquisition. Cross-language influence in third language acquisition studies can be analyzed from the first and second language role in the third language acquisition. Each acquisition Indonesian language as L3 is always English as L2 so that the role of English in acquiring Indonesian as B3 be worth studying. It is a qualitative approach based research. This study focuses on (1) the role of English of articulation and (2) the role of English as the provider acquiring vocabulary in Indonesian as L3. Data used in this research is the conversation conducted by the researcher and research subject; and sentence production based on picture by the research subject. Data analysis result finds 1) the role of English as an addition to the mastery of the sound that is not owned B1 of pemeroleh Indonesian as L3 and English influence language sounds in pronunciation Indonesian, and 2) The role of English as a provider of vocabulary in language acquisition Indonesia as B3 is as a language bridge in language acquisition Indonesia if the Indonesian pemeroleh not master words in Indonesian.